Determinación de la eficiencia de diferentes atrayentes naturales para el control del caracol gigante africano (Achatina fulica). - Chasi Pérez, Freddy Joel (2017)
The African giant snail (Achatina fulica) is an exotic species native to Africa, currently spread throughout South America. Situated in danger of flora and fauna. In 2005, in some provinces of the Ecuadorian littoral, one of the most important agricultural pests was the property of the "Dana Anais" estate, located in the Esperanza parish of Quevedo. The following natural attractants were tested: turnip greens, lettuce leaves, papaya, orange peel and beer. The trap consisted of polyethylene containers, cane stakes, and plastic sheaths. 5 × 5 Latin square design was used for experimentation. To avoid the aggregation effect of this pest, the traps were rotated periodically, so that each treatment had the opportunity to remain for one week at each site. As a result of this research it was determined that turnip leaves and beer had the greatest attraction to the African snail, catching an average of 39.8 and 36.8 snails per trap. On the other hand, the papaya was less effective, capturing an average of 21.4 snails per trap, being statistically inferior to the previous two. The implementation of this type of control with attractants for the snail does not contaminate the environment, it complies with an approach of organic agriculture and can be applied to different crops.